Cation-controlled chemoselective synthesis of N-aroylureas and imides via amidation of N-Boc arylamides. Issue 8 (24th March 2023) - Wang, Jiamin; Shuai, Sujuan; Gan, Lishe; Luo, Yongxin; Jin, Huimin; Chen, Lingfeng; Zou, Dong; Liang, Guang; Walsh, Patrick J.; Li, Jie
Abstract : In this study, the first highly chemoselective amidation of Boc and amide groups of N -R- N -Boc arylamides is advanced. Abstract : In this study, the first highly chemoselective amidation of Boc and amide groups of N -R- N -Boc arylamides is advanced. This practical and operationally-simple method enables the preparation of either N -aroylureas or imides in good to excellent yields without addition of transition metals. The choice of base plays a significant role in controlling the reactivity of the inequivalent carbonyl groups. The amidation of the Boc group was observed with arylamides, ArCONH2, when subjected to KO t Bu while imides were produced with LiOH. DFT studies are employed to explore the divergent mechanisms. It is anticipated that these chemoselective methods will be of interest to the synthetic and medicinal chemistry communities.